Development of pumice-copper catalyst for oxidation of methanol into formaldehyde - M. M. Davoudi; L. G. Bruk (Тонкие химические технологии, 2008)
Oxidation of methanol is the main method for the production of formaldehyde in industry. In order to expand the source of raw materials for the preparation of new catalyst for this process copper compounds as initial substances for obtaining the former are suggested. A number of catalysts obtained from various copper salts were tested; some of them are quite promising for further investigation.